Spatial analysis and attributable mortality to outdoor air pollutants in ‎Isfahan - Negar ‎ Jafari; amir mohammadi; Sepideh Nemati; Yaghoub Hajizadeh; Ahmmadreza Shirvani ‎; Ali Abdolahnejad; babak shiravand (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Long term exposure to air pollutants can result in the development and acceleration of various conditions, such as cardiac and respiratory problems, reduced lung function, chronic bronchitis, asthma, pulmonary cancer, and even death. Regarding this, the aim of the present study was to perform a spatial analysis of air pollution and mortality in Isfahan, Iran. Methods: In this ecological study, the spatial analysis of particulate matter 10 μm (PM10), PM2.5, ozone (O3), sulfur dioxide (SO2), and nitrogen dioxide (NO2) was performed using the geographic information system. Additionally, the evaluation of the premature deaths attributable to these pollutants was carried out through the AirQ software version 2.2. Results: According to the results of the spatial analysis, the eastern part of Isfahan had higher concentration of air pollutants, compared to other directions. There were 481, 493, 117, 102, and 54 mortality cases attributed to PM10, PM2.5, O3, SO2, and NO2, respectively. In addition, PM10 was found to have the highest health effects among other pollutants. Conclusion: As the findings of this study indicated, PM10 had the highest concentration in Isfahan city. With respect to the fact that air pollutants accounted for almost 15.8% of the total mortality rate in this city, there is an argent need to adapt some strategies to reduce the emissions of air pollutants.